Frequency of Adhesive Intestinal Obstruction following Gynecologic Surgery - Bushra Nabi, Asif Mehmood (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Adhesive intestinal obstruction (AIO) is a frequent and severe postoperative complication of abdominopelvic surgery, especially of gynecologic surgeries. It is the cause of morbidity in patients, recurrent hospitalizations and augmented medical charge. Although there has been a rise in surgical methods, AIO has continued to be a clinical issue, particularly in those clinical environments whereby open gynecologic surgeries are commonly conducted. Objective: To establish the incidence of adhesive intestinal obstruction in the aftermath of gynecologic surgery in a tertiary care hospital. Methods: It is a retrospective observational study that took place in a Khalifa Gul Nawaz Teaching Hospital Bannu during the period April 2023 to September 2023. The review of hospital records concerning women who had undergone gynecologic surgery was conducted and the cases that were subsequently admitted with intestinal obstruction were identified. The diagnosis of adhesive intestinal obstruction was done on the clinical feature, the basic radiological results and operative confirmation where necessary. The descriptive statistics were applied to analyze the data about patient demographics, type of gynecologic surgery, time interval to presentation, and management outcomes. Results: Among 1,246 gynecologic surgeries performed in the study, 64 patients experienced adhesive intestinal obstruction and a frequency of 5.1 was obtained. The highest age-related group that was most affected was the 41 50 years age group. The most commonly associated procedure was total abdominal hysterectomy. Almost 50 percent of the patients were reported in less than one year of surgery. In 65.6% the conservative management was successful and in 34.4% surgery was necessary. Conclusion: Adhesive bowel obstruction is an observable complication after gynaecologic surgery and a considerable percentage of patients would need to be admitted and treated. The morbidity that is associated with it should be minimized through preventive surgical measures and early diagnosis. Keywords: Adhesive intestinal obstruction; Gynecologic surgery; Postoperative complications; Intestinal obstruction.